Two new multi-path routing algorithms for fault-tolerant communications in smart grid - Hong, Yi; Kim, Donghyun; Li, Deying; Guo, Ling; Son, Junggab; Tokuta, Alade O. (Ad hoc networks, 2014)
Recently, smart grid, which is a newer generation of electricity supply network, is getting lots of attentions due to its huge benefits. One key component of the smart gird is an integrated communication network. To make the smart grid more dependable, it is extremely important to ensure that messages are exchanged over the communication network in a reliable and timely manner. A multiple path routing might be one way to achieve this goal. Unfortunately, the existing algorithms which compute multiple node-disjoint paths are not sufficient for this purpose since in a smart grid communication network, node failures can be co-related. Motivated by this observation, we introduce a new quality multiple routing path computation problem in a smart grid communication network, namely the min–max non-disrupting k path computation problem (M2NkPCP). We show this problem is NP-hard and propose two heuristic algorithms for it. In addition, we evaluate the average performance of the algorithms via simulation.